Metamorphic evolution and tectonic significance of ultrahigh‐temperature mafic granulites in the southern part of the Shiguai area, Daqingshan, China. (4th September 2019) - Yang, Yan; Liang, Chenyue; Zheng, Changqing; Zhang, Jinrui; Xu, Xuechun; Guo, Tengda; Zhou, Xiao; Hu, Pengyue; Han, Xiaomeng; Hao, Yujie
Abstract : Ultrahigh‐temperature (UHT) mafic granulites in the southern part of the Shiguai area in Daqingshan, China, crop out within the Shanheyuan Gneiss of the Khondalite Belt (KB), a Paleoproterozoic tectonic belt in the Western Block of the North China Craton (NCC). The UHT mafic granulites occur within hypersthene‐bearing dioritic–granitic gneiss as irregular lenses and deformed dike swarms. Four metamorphic generation assemblages (M1 –M4 ) are recognized in the studied samples. M1 is defined by the enclosed orthopyroxene and clinopyroxene within the "red eye" corona of the garnet, representing the prograde metamorphic stage. M2 (UHT granulite‐facies) is marked by the appearance of "red eye" corona of the garnet, with mineral assemblages of grt–cpx–opx–pl–ilm–q. M3 is defined by spinel‐rich symplectites between garnet and orthopyroxene, including grt–opx–pl–spl–mt–ilm. M4 (amphibolite facies) is featured by the development of amphibole. Phase equilibrium modelling and some critical thermobarometers are combined to constrain the P–T evolution of the studied samples. The P–T conditions for the M1 – M4 are respectively estimated at ~8 kbar/~771–852°C, ~9.4–10.0 kbar/~930–965°C, ~5.0–5.4 kbar/~865–910°C, ~5.0–5.2 kbar/~675–682°C, which define a clockwise P–T path, involving near‐isothermal decompression following the peak metamorphism. The P–T path indicates that the rocks underwent a sequence of tectonothermal processes that started with crustal thickening (M1 – M2 ), followed by rapid crustal uplift (M3 ) and cooling (M4 ). This process is inferred that the metamorphism of the UHT mafic granulites was associated with rapid exhumation and uplift that followed the continent–continent collision and amalgamation of the Yinshan and Ordos blocks. This amalgamation formed the Paleoproterozoic KB in the Western Block of the NCC.